Imperialism, race, and resistance - Bush, Barbara (London Routledge, 1999)
Imperialism, Race and Resistance marks an important new development in the study of British and imperial interwar history.
Includes bibliographical references (p. [344]-375) and index.
Keywords: Africa, English-speaking West--Politics and government--20th century